Pengaruh Pupuk Kombinasi Urea – Zeolit - Arang Aktif (UZAA) terhadap pH, Eh, Amonium dan Nitrat pada Tanah Sawah Rancaekek, Kabupaten Bandung - Restiana Maulinda; Maya Damayani; Benny Joy (Fakultas Pertanian Universitas Padjadjaran, 2017)
Urea is N fertilizer that often used by Indonesian’s famers. Zeolite and activated charcoal is known to be able to increase efficiency Nitrogen from urea fertilizer on paddy soils. This research was conducted to study the urea-zeolite-activated charcoal fertilizer combination for acidity (pH), Redox Potential (Eh) level, slow release NH4+ (ammonium) and NO3-(nitrate) on paddy soils. Experiment was carried out at greenhouse and experimental field, Departement of Soil Science and Land Resources Management, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The experimental design was Randomized Block Design consisted of five treatments and five replications. The treatments consisted of A (control), B (50% Urea + 25% Zeolite + 25% Activated charcoal), C (50% Urea + 45% Zeolite + 5% Activated charcoal), D (60% Urea + 40% Zeolite) and E (95% Urea + 5% Zeolite). Experimental result showed that the application zeolite and activated charcoal increased the pH and decreasead Eh level. Application of urea-zeolite-activated charcoal fertilizer (50%:45%:5%) is the best for slow release ammonium. This experiment showed that application of Urea-Zeolite-Activated Charcoal (UZAA) fertilizer could reduce the usage of urea fertilizer.Keyword: urea, zeolite, activated charcoal